Discovery Learning: Its Impact on Students’ Mathematical Computational Thinking Ability and Self-Confidence - Irfi Windari; Fatra, Maifalinda; Diwidian, Femmy (JNPM (Jurnal Nasional Pendidikan Matematika), 2025)
Computational thinking is the ability to think about solving problems the way a computer works. This ability is very important in the 21st century, so it needs a teacher's attention when teaching mathematics. This study aims to explore and analyze the impact of discovery learning on students' mathematical computational thinking abilities and self-confidence. The research was carried out at a private high school in Bogor for the 2023/2024 academic year. This research uses a quasi-experimental method with a randomized posttest-only control group design. The research sample consisted of 28 students using the discovery learning model and 26 students using the conventional model. Data collection instruments are tests and questionnaires that have been tested for validity and reliability. The research results show that the average mathematical computational thinking ability taught using the discovery learning model is higher than the conventional model class, with a large influence in the medium category (= 0.221). The average self-confidence of experimental class students is higher than that of the control class with large being included in the medium category (= 0.186). The discovery learning model influences students' mathematical computational thinking abilities and self-confidence in the high category (= 0.292).